Negotiating the past in the past: identity, memory, and landscape in archaeological research - Yoffee, Norman (University of Arizona Press, 2007)
Peering into the palimpsest : an introduction to the volume / Norman Yoffee -- Collecting, defacing, reinscribing (and otherwise performing) memory in the ancient world / Catherine Lyon Crawford -- Unforgettable landscapes : attachments to the past in Hellenistic Armenia / Lori Khatchadourian -- Mortuary studies, memory, and the Mycenaean polity / Seth Button -- Identity under construction in Roman Athens / Sanjaya Thakur -- Inscribing the Napatan landscape : architecture and royal identity / Lindsay Ambridge -- Negotiated pasts and the memorialized present in ancient India : Chalukyas of Vatapi / Hemanth Kadambi -- Creating, transforming, rejecting, and reinterpreting ancient Maya urban landscapes : insights from Lagartera and Margarita / Laura P. Villamil -- Back to the future : from the past in the present to the past in the past / Lynn Meskell -- Memory groups and the state : erasing the past and inscribing the present in the landscapes of the Mediterranean and Near East / Jack L. Davis